Peranan Stres Akademik Terhadap Kecanduan Game Online pada Mahasiswa Tingkat Akhir - Veebie Cleodora Valein; Agustina (STKIP Subang, 2026)
This study aims to examine the role of academic stress on online game addiction among final-year university students who are currently completing their thesis. The increasing academic demands, deadlines, and emotional pressure during the thesis process often become significant sources of stress. As a result, many students tend to cope with their stress by engaging in online gaming activities. The participants of this study were 192 final-year students who actively play online games. Data were collected using two measurement instruments: an academic stress scale adapted from Rifaldi (2020) and the Indonesian Game Addiction Questionnaire (IGAQ) developed by Jap et al. (2013). The data were analyzed using correlation and simple linear regression. The results indicate a significant and positive relationship between academic stress and online game addiction. Furthermore, academic stress contributes 47.7% to the increase in online game addiction, while the remaining percentage is influenced by other factors not examined in this study. These findings suggest that academic stress is one of the dominant predictors of online game addiction among final-year students. Therefore, the use of online games as a coping strategy has the potential to develop into maladaptive behavior when stress is not managed properly.